Technology-mediated financial education in developing countries: a systematic literature review - Abebe Walle Menberu (Cogent Business & Management, 2024)
Financial education mediated by technology has the potential to reduce disparities in financial literacy in developing countries. Technology-mediated financial education provides numerous advantages, such as scalability, cost-effectiveness, adaptability and the capacity to reach underserved populations. Nevertheless, it is important to acknowledge the existence of certain obstacles in this context. These challenges encompass issues such as insufficient infrastructure, disparities in access, language and cultural barriers, as well as the exclusion of marginalized communities. This research article critically examines the existing body of literature on Technology mediated financial education in developing countries and highlights three significant domains that warrant further investigation: comprehensive evaluations of long-term effects, comparative analyses of different delivery approaches and the development of inclusive research methodologies. The research also provides suggestions for policymakers, educators and practitioners, which encompass investing in digital infrastructure, engaging in collaborative efforts with stakeholders, designing customized interventions and implementing comprehensive monitoring and evaluation frameworks.
Keywords: 650; Financial literacy; technology-mediated financial education; developing countries